Glacial melt impacts carbon flows in an Antarctic benthic food web - Braeckman, Ulrike (2024)
Most coastal glaciers on the West Antarctic Peninsula are in retreat. Glacial ice scouring and lithogenic particle runoff increase turbidity and shape soft sediment benthic communities. This, in turn, has the potential to induce a shift in these systems from an autotrophic to a heterotrophic state. In this study, we investigated the influence of glacial runoff on carbon flows in the softsediment food web of Potter Cove, a well-studied shallow fjord located in the northern region of the West Antarctic Peninsula. We constructed linear inverse food web models using a dataset that includes benthic carbon stocks as well as carbon production and respiration rates. The dataset offers detailed spatial information across three locations and seasonal variations spanning three seasons, reflecting different degrees of disturbance from glacial melt runoff. In these highly resolved food web models, we quantified the carbon flows from various resource compartments (phytoplankton detritus, macroalgae, microphytobenthos, sediment detritus) to consumers (ranging from prokaryotes to various functional groups in meio- and macrofauna). Locations and seasons characterized by high glacial melt runoff exhibited distinct patterns of carbon flow compared to those with low glacial melt runoff. This difference was primarily driven by a less pronounced benthic primary production pathway, an impaired microbial loop and a lower secondary production of the dominant bivalve Aequiyoldia eightsii and other infauna in the location close to the glacier. In contrast, the bivalve Laternula elliptica and meiofauna had the highest secondary production close to the glacier, where they are exposed to high glacial melt runoff. This study shows how the effects of glacial melt propagate from lower to higher trophic levels, thereby affecting the transfer of energy in the ecosystem.